The use of supplementary materials in EFL classes: a comparative analysis of public and private schools - Lara Mejia, Diana Carolina (2013)
The purpose of this present study was to know whether or not supplementary materials are used in a pertinent, appropriate, and qualified way by EFL teachers. To conduct the research, two high schools, one public and one private, were selected, observing English lessons in first, second, and third years. In the present research study, thirty classes were observed, fifteen in each school. During each observed lesson, notes were taken to fill-in a description sheet about the use of supplementary materials. Based on this information, it was possible to complete qualitative tabulation charts about the types of supplementary materials used in public and private high schools which provided evidence whether teachers use supplementary materials in a pertinent and appropriate manner, taking into account the objective of the class, level, and student’s age. The quantitative tabulation charts also were used in order to obtain the results of the frequency of supplementary materials used in 1st, 2nd, and 3rd years of public and private high schools. The results revealed that the most used materials in both institutions were the whiteboard and handouts